Python GUI programming : a complete reference guide : develop responsive and powerful GUI applications with PyQt and Tkinter /: a complete reference guide : develop responsive and powerful GUI applications with PyQt and Tkinter. (2019) - Moore, Alan, 1961-; Harwani, B. M
No abstract available